2019
DOI: 10.3390/ijms20122877
|View full text |Cite
|
Sign up to set email alerts
|

Early Immunological Effects of Ischemia-Reperfusion Injury: No Modulation by Ischemic Preconditioning in a Randomised Crossover Trial in Healthy Humans

Abstract: Ischemic preconditioning (IPC) has been protective against ischemia-reperfusion injury (IRI), but the underlying mechanism is poorly understood. We examined whether IPC modulates the early inflammatory response after IRI. Nineteen healthy males participated in a randomised crossover trial with and without IPC before IRI. IPC and IRI were performed by cuff inflation on the forearm. IPC consisted of four cycles of five minutes followed by five minutes of reperfusion. IRI consisted of twenty minutes followed by 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Thus, RIC is unable to attenuate IRI in the setting of deceased donor kidney transplantation to an extent that can be detected as clinical, biochemical or immunological parameters. These findings are in line with the results of RIC in healthy volunteers, showing that there are no major immune modulations within the first 24 h after ischaemic preconditioning [28].…”
Section: Discussionsupporting
confidence: 90%
“…Thus, RIC is unable to attenuate IRI in the setting of deceased donor kidney transplantation to an extent that can be detected as clinical, biochemical or immunological parameters. These findings are in line with the results of RIC in healthy volunteers, showing that there are no major immune modulations within the first 24 h after ischaemic preconditioning [28].…”
Section: Discussionsupporting
confidence: 90%
“…Oxidative stress biomarkers seem to be far from reflecting the results of I/R damage quickly enough to be useful in surgery. A study that evaluated the effects of ischemic preconditioning on I/R injury found that inflammatory cytokine levels were not significantly affected by I/R injury 31 . It seems that inflammatory markers do not give as much information as the markers we are used to.…”
Section: Discussionmentioning
confidence: 96%
“…There is accumulating evidence indicating that T cells, particularly CD4 + T cells, play a critical role in the pathogenesis of renal I/R [10,12,13]. However, the mechanism of T 10 Disease Markers cell infiltration during the early phase of renal IRI remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…As an acute tissue injury, renal I/R injury leads to infiltration of immune cells, which contributes to both the damage and repair processes together with resident immune cells [ 2 , 9 , 11 ]. Numerous studies have shown that T cells exploit extremely complex functions in renal ischemic response [ 10 , 12 , 13 ]. A few studies utilizing selective knockout rodents and CD4 + and/or CD8 + reconstituted T cell subsets have implicated that CD4 + cells promote damage during the early stage after ischemia [ 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%